The Effect of Early Self-Detection of Diabetes Mellitus on the Healthy Behavior of DM Risk Groups Based on Health Belief Model (HBM) - Agus Priyanto; Eko Dian Hadi Suprayetno; Titik Juwariah; Jovi Sulaiman (Journal of Ners and Midwifery, 2024)
Diabetes mellitus is a health problem throughout the world, and its prevalence continues to increase every year. Diabetes mellitus is often not realized by diabetics because it does not produce typical symptoms in the early period. Diabetes is a non-communicable disease (NCD) because of 80% unhealthy behavior. The problem in this research is that the diabetes risk group cannot yet carry out independent early detection of diabetes; they are not aware of their health conditions related to the incidence of DM, so they have not made efforts to change behavior to prevent diabetes mellitus and reduce risk factors that can be changed. This research aimed to determine the effect of early self-detection of diabetes mellitus on the health behavior of DM risk groups based on the Health Belief Model (HBM). This quantitative research used a quasi-experiment design with a one-group pre-post-test approach. The sample was 100 respondents by purposive sampling. The data collection used questionnaires based on HBM. The research intervention was by teaching the use of the SEDAB application and educating on healthy behavior to prevent DM; the interval between intervention and post-test was 4 weeks. Analysis of research data uses the Wilcoxon Signed Rank Test. The research results show that the intervention has the effect of increasing perceived susceptibility (p-value=0.000), Perceived Severity (p-value=0.000), Perceived Barriers (p-value=0.000), Perceived Benefit Perceived (p-value=0.000), cues to action (p-value=0.017), Self-efficacy (p-value=0.000), and healthy behavior (p-value=0.000). Early detection of diabetes in diabetes risk groups is essential to prevent DM and improve healthier lifestyles.